Acoustic Parameters for Optimizing Lung Volume During High- Frequency Oscillatory Ventilation in Infants with Respiratory Distress Syndrome: A Feasibility Study - Luria, Oded; Kohelet, David; Barnea, Ofer (The open medical devices journal, 2010)
During high-frequency oscillatory ventilation (HFOV), the primary variable affecting lung volume is the mean airway pressure (MAP). To effectively maintain lung recruitment and optimal gas exchange without overstretching (or collapsing) the lung, MAP should be set between the lower and upper inflection points of the pressure-volume curve of the lung. At present, there is no efficacious means that allows the neonatologist to determine the MAP (optimal MAP) which attains optimal lung expansion and avoids overdistension. Thus, MAP is usually adjusted by trial and error or by clinical experience of the user. In this study, we investigated the acoustic properties of the neonate lung in six newborns undergoing high frequency oscillatory ventilation, to assess its usefulness as a means for determining optimal mean airway pressure. We found that the shape of the acoustic reflection-pressure curve was similar to the shape of the known pressure-volume curve. In all subjects, the estimated range of MAP was in congruence with the pressure chosen by the neonatologist. The acoustic measurements indicated of an increase in lung volume following administration of exogenous surfactant. Hysteresis in the amplitude of acoustic reflection was measured as expected. Our results indicate that the acoustic technique provides useful information about the state of lung recruitment during HFOV and may be helpful in identifying the adequate MAP for optimal lung expansion without overdistension.